Short-Term and Mid-Term Clinical Outcomes Following Hybrid Coronary Revascularization Versus Off-Pump Coronary Artery Bypass: A Meta-Analysis - Dong,Li (2018)
Abstract Background: Off-pump coronary artery bypass grafting (OPCAB) is one of the standard treatments for coronary artery disease (CAD) while hybrid coronary revascularization (HCR) represents an evolving revascularization strategy. However, the difference in outcomes between them remains unclear. Objective: We performed a meta-analysis to compare the short-term and mid-term outcomes of HCR versus OPCAB for the treatment of multivessel or left main CAD. Methods: We searched the PubMed, EMBASE, Web of Science and Cochrane databases to identify related studies and a routine meta-analysis was conducted. Results: Nine studies with 6121 patients were included in the analysis. There was no significant difference in short-term major adverse cardiac and cerebrovascular event (MACCE) rate (RR: 0.55, 95% CI: 0.30-1.03, p = 0.06) or mortality (RR: 0.51, 95% CI: 0.17-1.48, p = 0.22). HCR required less ventilator time (SMD: -0.36, 95% CI: -0.55- -0.16, p < 0.001), ICU stay (SMD: -0.35, 95% CI: -0.58 - -0.13, p < 0.01), hospital stay (SMD: -0.29, 95% CI: -0.50- -0.07, p < 0.05) and blood transfusion rate (RR: 0.57, 95% CI: 0.49-0.67, p < 0.001), but needed more operation time (SMD: 1.29, 95% CI: 0.54-2.05, p < 0.001) and hospitalization costs (SMD: 1.06, 95% CI: 0.45-1.66, p < 0.001). The HCR group had lower mid-term MACCE rate (RR: 0.49, 95% CI: 0.26-0.92, p < 0.05) but higher rate in mid-term target vessel revascularization (TVR, RR: 2.20, 95% CI: 1.32-3.67, p < 0.01). Conclusions: HCR had similar short-term mortality and morbidity comparing to OPCAB. HCR decreased the ventilator time, ICU stay, hospital stay, blood transfusion rate and increased operation time and hospitalization costs. HCR has a lower mid-term MACCE rate while OPCAB shows better in mid-term TVR.